A new species of Eufriesea from Jalisco, México, with a key to Mexican species of the genus (Hymenoptera: Apidae). - Ayala, Ricardo; Engel, Michael S. (Contributions to Entomology = Beiträge zur Entomologie, 2008)
A new species of the orchid bee genus Eufriesea Cockerell (Apidae: Apinae: Euglossini) is described and figured. Eufriesea micheneri sp. n. is generally similar to E. caerulescens (Lepeletier de Saint Fargeau) with is dark blue integument and purple iridescence but differs by its black pubescence, dark wings, and in the male by its green facial integument and terminalia. The new species is known from the Sierra del Tuito in Jalisco State, México, a western part of the Transverse Volcanic Belt. A key for the Mexican species of Eufriesea is provided in English and Spanish.ResumenSe describe una nueva especie de abeja del género Eufriesea Cockerell (Apidae: Apinae: Euglossini) con integumento azul oscuro e iridiscencia morada, similar en apariencia a Eufriesea caerulescens (Lepeletier de Saint Fargeau), de la cual puede ser fácilmente diferenciada por presentar pubescencia negra, alas más oscuras y en el caso de los machos el área facial con integumento verde metálico. Esta especie se conoce únicamente para la Sierra del Tuito, en el extremo más Oeste del Eje Volcánico Transversal, en el estado de Jalisco, México. Se incluye una clave para el reconocimiento de las especies mexicanas en ingles y español.KeywordsHymenoptera, Apoidea, Anthophila, Euglossini, taxonomy, México.Nomenclatural Actsmicheneri Ayala & Engel, 2008 (Eufriesea), spec. n.